Product Selection of Face Masks for Sensitive Skin Using the Composite Performance Index (CPI) Method - Nugroho, Prasetiyanto; Azhari, Ahmad (Signal and Image Processing Letters, 2023)
The more face mask products for sensitive facial skin that are created, consumers also feel confused by several considerations such as excessive side effects for the mask products they will use so as not to worsen the condition of the facial skin. Therefore, to help consumers in choosing the right face mask in terms of consideration of benefits, side effects that will be caused, and affordable prices, the authors compiled a study with the title "Selection of Face Mask Products for Sensitive Skin Using the Composite Performance Index (CPI) Method". Composite Performance Index (CPI) was chosen because this method is good at decision making and the calculation process of the CPI method only requires the criteria value of several alternatives which when compared to the CPI method process is shorter. This method can be used to determine the assessment or ranking of various alternatives based on several criteria. Criteria values are inputs that have been entered and converted into numbers. While the alternative value is the weighting obtained from the calculation of multiplication, addition of ingredients or division of each criterion. The result of this research is that the assessment process can be carried out from each mask product using the criteria of price, skin condition, mask benefits and consumer age. The system can determine the best mask for sensitive skin by implementing the Composite Performance Index (CPI) method with the results of the website validity test getting a percentage of 85.34% with a very good interpretation.